Diagnosing Carpal Tunnel Syndrome by Ultrasound - Mamoona Chiragh, (Journal of Rawalpindi Medical College, 2009)
Background Carpal tunnel syndrome (CTS) is traditionally diagnosed by clinical evaluation and nerve conduction studies (NCS). Ultrasound is now widely used in the diagnosis of musculoskeletal disorders. The objective of this study was to compare the sonographic measurements of median nerve in patients of CTS with NCS results, taking NCS as gold standard and to evaluate the diagnostic role of ultrasound so that it could be used in the diagnosis of CTS. Methods: This cross sectional Analytical study was carried out at Department of Radiology, Combined Military Hospital Lahore over a period of one year from 21st August 2006 to 20th August 2007. One hundred and twenty wrists in sixty CTS patients were imaged by high resolution ultrasound. The cross sectional area of the median nerve was measured at the level of pisiform bone. All patients had nerve conduction studies. The ultrasound measurements of the median nerve cross sectional area and the results of nerve conduction studies were compared and analyzed. Results: The mean cross sectional area of the median nerve at the level of pisifom was 13mm2 in CTS patients. When NCS results were taken as gold standard, the ultrasound yielded a sensitivity of 94.7%, specificity of 63.6% and diagnostic accuracy of 87.8%. Conclusion: High resolution ultrasound is quite accurate and it can be used reliably and cost effectively in the diagnosis of CTS especially for screening of large population of CTS patients.